2021
DOI: 10.1177/00910260211034213
|View full text |Cite
|
Sign up to set email alerts
|

Faking Versus Feeling Emotions: Does Personality–Job Fit Make a Difference

Abstract: Emotional labor (EL) involves regulating, managing, and sensing others’ emotions to achieve organizational goals. However, it is often considered a unitary variable, without examining the specific types of emotional labor (i.e., deep acting and surface acting). Thus, the purpose of this research is to extend the under-researched work on surface-acting and deep-acting strategies of EL on job involvement in the public sector by examining the mediating effects of personality–job fit. This research employs the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…The experience of close contact with clients is often fraught with conflicts and tensions arising from unpleasant communication, contradictory expectations, or limited resources (Grandey & Diamond, 2010). Under such a demanding environment, it becomes challenging to induce JS among street-level bureaucrats if their motivation for serving the public is not sufficiently steadfast to overcome the predicaments at work (Wen et al, 2020; Zvobgo et al, 2022). Imaginably, highly motivated public servants are more likely to deal with their job demands with ease and prevent exhaustion (Bakker, 2015; Mussagulova, 2021).…”
Section: Analytical Framework and Hypothesesmentioning
confidence: 99%
“…The experience of close contact with clients is often fraught with conflicts and tensions arising from unpleasant communication, contradictory expectations, or limited resources (Grandey & Diamond, 2010). Under such a demanding environment, it becomes challenging to induce JS among street-level bureaucrats if their motivation for serving the public is not sufficiently steadfast to overcome the predicaments at work (Wen et al, 2020; Zvobgo et al, 2022). Imaginably, highly motivated public servants are more likely to deal with their job demands with ease and prevent exhaustion (Bakker, 2015; Mussagulova, 2021).…”
Section: Analytical Framework and Hypothesesmentioning
confidence: 99%
“…Thus, they are better able to utilize commonly known "display rules" that are associated with emotional labor, than employees with lesser political skills. However, research on emotional dissonance has shown that such experiences are very uncomfortable for employees, and employees might become ultimately motivated to quit the emotional dissonance that occurs (Zvobgo, Abraham, & Sabharwal, 2021). Also, there exists significant evidence between emotional labor strategies and turnover intention; especially surface acting (Kang & Jang, 2022).…”
Section: Background Of the Studymentioning
confidence: 99%